How Many Types of Dystonia? Pathophysiological Considerations - Quartarone, Angelo; Ruge, Diane (Frontiers in Neurology, 2018)
Dystonia can be seen in a number of different phenotypes that may arise from different aetiologies. The pathophysiological substrate of dystonia is related to three lines of research. The first postulate a loss of inhibition which may account for the excess of movement and for the overflow phenomena. A second abnormality is sensory dysfunction which is related to the mild sensory complaints in patients with focal dystonias and may be responsible for some of the motor dysfunction. Finally there are strong evidences form animal and human studies suggesting that alterations of synaptic plasticity characterized by a disruption of homeostatic plasticity, with a prevailing facilitation of synaptic potentiation may play a pivotal role in primary dystonia. These working hypotheses have been generalized in all form of dystonia. On the other hand, several evidences now suggest that the pathophysiology may be slightly different in the different types of dystonia. Therefore in the present review we would like to discuss the neural mechanisms underlying the different forms of dystonia to disentangle the different weight and role of environmental and predisposing factors.